Global research trends in the subjective well-being of older adults from 2002 to 2021: A bibliometric analysis - Huang, Derong; Wang, Jian; Fang, Huiling; Wang, Xuehan; Zhang, Yujie; Cao, Shuo (Frontiers in Psychology, 2022)
Purpose: The study aimed to explore current developments and trends in the field of subjective well-being (SWB) of older adults at a macro level and identify research hotspots. Methods: We included reviews or articles on the SWB of older adults in the Web of Science Core Collection published from 2002 to 2021. We used CiteSpace to draw a knowledge map of the authors, institutions, countries, references, and keywords for visual analysis and used Microsoft Excel tables to count basic information details. Results: A total of 354 papers were included, and the number of papers published over the past two decades showed a pattern of growth. The core force of publications was primarily attributed to studies conducted in Europe, North America, Asia, and Oceania, which have relatively major issues of aging and good economic strength. However, links between states, institutions, and authors were relatively weak. Cluster analysis showed that the research field could be divided into eight topics: the application of social psychology in the study of the SWB of older adults, aging in older adults, health condition of older adults, achieving successful aging, interventions for SWB, age differences in SWB research, an economic perspective of SWB research and social support for older adults. Current research frontiers are socioeconomic status, community, intervention, participation, adjustment, validation, and personality. Conclusion: The results of the present study provided a comprehensive picture in the research field of SWB of older adults. It showed that the mechanism, especially the bidirectional effect, between the SWB of older adults and its influencing factors is still worthy of further exploration. More research on evidence-based and intervention strategies should be conducted in the future.